The art of entrepreneurial pursuit social commerce through the lived experiences of facebook live-sellers in the Philippines - Labio, Princess Annielour L. (2022)
Dennison, Bourdage-Braun, and Chetuparambil (2009, 2) strongly emphasize that??social commerce is [the concept of] word of mouth applied to e-commerce?. This has been found advantageous to sellers and buyers alike as it is offers lower production costs, but higher engagements and sales. Live s-commerce offers a dynamic mode of online shopping wherein goods are (virtually) introduced to consumers in real-time by the streamer/s. its audio-visual system enables viewers to ?assess? commodities as if they were physically present in a store. (Wongkitrungrueng and Assarut 2020). There is a need to observe and analyze the mechanisms involved in social commerce for its utilization is rapidly increasing amid the ongoing pandemic. The present study has the following objectives: (1) to identify issues in social commerce; (2) to describe the experiences of the actors involved, that is, live sellers; and (3) to determine whether cultural norms/practices affect social commerce transactions. The findings of the study suggest that economic studies should delve more into entrepreneurs? point of view so as to have a clearer picture of what a market is, its function, and how it operates. The mechanisms behind live s-commerce are not merely anchored in technological features, but also in other factors such as language, atmosphere, and social interactions. It is a type of social commerce that is more dynamic, yet extremely complex in terms of organization and process. Social commerce is a cultural phenomenon as well as due to the evident presence of local constructs and concepts within its entire system. Norms and practices dating back centuries ago are still being materialized in spite of the reducible and waning effects of modern technology. Exchanges are extended to the real world, solidified by personal interactions, and reinforced through recurring meetings